Variation of blood pressure between two arms among the young people of Guwahati, Assam, India - Das, Indrani; Bora, Bonti; Sarkar, Raj; Bhuyan, Kaustuv Jyoti (International Journal of Research in Medical Sciences, 2018)
Background: Aim and objective of the study was to determine whether a difference in systolic and diastolic blood pressure reading exists in between arms. To establish the mean and normal range of difference in simultaneous systolic and diastolic blood pressure measurements between the right and left arm. It is unclear to what extent inter-arm blood pressure (BP) differences may be present in younger people so that they can take precaution in relation with age. Methods: 51 male and 51 female subjects were selected randomly in age group of 18 -20 yrs. A normal mercury sphygmomanometer was used employing Korotkoff I and V. 3 readings were taken sequentially for each arm using a standard mercury sphygmomanometer with the subject sitting after resting for 10 min. Results: Mean ± SD inter-arm differences in Systolic blood pressure were 4.784 ± 6.338 mmHg in males and 2.314 ± 5.159 mmHg in females while Diastolic blood pressure were 3.451 ± 5.471 mmHg in males and 1.059 ± 5.112 mmHg in females. Conclusions: The frequency of significant inter-arm systolic and diastolic blood pressure differences suggests that the blood pressure should be taken in both arms at the initial consultation. At subsequent visits, the arm in which measurements are taken should be recorded in the case notes. The higher of the two readings should be used to guide further management decisions. The accurate assessment of blood pressure (BP) is vital for the correct diagnosis and treatment of hypertension.